Regard sur l’interaction de l’urbanisation, du traumatisme historique et de l’identité culturelle parmi la jeunesse autochtone au Canada - Fast, Elizabeth; Nutton, Jennifer; De La Sablonnière-Griffin, Mireille; Kozlowski, Anna; Bertrand, Nahka; Bertrand, Swaneige; Mitchell, Jennifer (Centre Urbanisation Culture Société (UCS) de l'INRS, 2017)
Urbanization is a form of ongoing colonization of Indigenous peoples (Taylor and Bell, 2004). It is a consequence of historical trauma – a culmination of losses suffered by Indigenous peoples in Canada as a result of colonialism that has manifested as trauma symptoms such as higher rates of addiction, mental health problems, and family violence (Criminal Code, R.S.C., 1985, c. C-46; Brave Heart, 1998; Evans-Campbell, 2008; Wesley-Esquimaux and Smolewski, 2004). It is also a symptom of current colonialist conditions, such as infrastructure deficiencies that force people to leave their home communities to work, undertake higher education or, in many cases, receive essential medical care. Using interviews from a larger study that explored the cultural identity of urban Indigenous youth in Montreal, we illustrate how urbanization, historical trauma, and cultural identity interplay in the lives of the youth interviewed for this study. The study operationalized OCAP® principles by having a committee comprised of urban Indigenous youth oversee all aspects of the research process (CPN, 2007). The analysis identified four broad themes interconnecting urbanization, historical trauma, and cultural identity. First, participants identified the ways in which historical trauma impacted their lives. Their discourse converged to identify urbanization as a form of ongoing colonial policy and of historical trauma. Finally, the youth discussed their experiences of racism and stereotypes in urban settings and how this affected their sense of cultural identity. We illustrate how urbanization, historical trauma, and cultural identity interplay in the lives of the youth interviewed for this study. L’urbanisation est une forme de colonisation actuelle des peuples autochtones (Taylor et Bell, 2004). Elle est, d’une part, une conséquence d’un traumatisme historique, soit l’aboutissement des pertes subies par les peuples autochtones au Canada en raison du colonialisme, qui s’est traduit par des manifestations comprenant une incidence ...